Harmoniousness Essays in Chinese Musicology - Jao, Tsung-i (Brill, 2022)
From prehistoric bone flutes to Confucian bell-sets, from ancient divination to his beloved qin, this book presents translations of thirteen seminal essays on musical subjects by Jao Tsung-i. In language as elegant and refined as the ancient texts he so admired, his journey takes readers through Buddhist incantation, the philosophy of musical instruments, acoustical numerology, lyric poetry, historical and sociological contexts, manuscript studies, dance choreography, repertoire formulation, and opera texts. His voice is authoritative and intimate, the expert crafting his arguments, both accessible and sophisticated, succinct and richly tapestried; and concealed within a deft modesty is a thinker privileging us with his most profound observation. The musician's musician, the scholar's scholar, bold yet cautious, flamboyant yet restrained, a man for all seasons, a harmoniousness of time and place.